The Effect of motivation on the productivity of the employees of sport departments of Ardabil province - Imanzadeh, Masoud; Gundogdu, Camal (My University, 2011)
Today, there is an agreement on the high value of human resources of every organization as an invaluable asset. One of the main concerning of managers is having highly motivated human resources (Ali, 2003). Among all organizations, having highly motivated human resources in the sport departments is very important. In this study, that was in 2010; the effect of motivation on the productivity of employees of sport departments of Ardabil province has been assessed. The samples of this study are 150 persons (15 females and 135 males) and all of them have been taken part in every steps of this study. The effective factors such welfare, work condition and environmental factors on the motivation have been sassed through a questionnaire of 30 questions and the result has been calculated and analyzed by SPSS. At the end, it is concluded that there is a significant and positive relationship between the motivation and the environmental factors and the degree of productivity of employees of sport departments of Ardabil province.
Keywords: Motivation; Physical education; Productivity; Sport; Sport management